Mobile payment as a multi-sided platform : Success factors and IT governance practices - Iivanainen, Ella (fi=Turun yliopisto|en=University of Turku|, 2017)
The aim of this research was to discover factors that lead to mobile payment platform’s success in the Finnish market. Mobile payment research has been ongoing for the past 20 years but no solution has made a clear breakthrough. Research has focused on technological factors, factors concerning consumers and adoption of mobile payment solutions and the majority has been exploratory, early research. Because of the rise of mobile technology and popularity of mobile content, flexible use of mobile phones and growing amount of non-cash transactions is a turning point now possible for mobile payment solutions. Along the success factors this research aimed to consider governance practices and to examine the perceived roles of the ecosystem participants. This is a qualitative study based on a case, MobilePay, a mobile payment platform provided by Danske Bank. Eleven semi-structured interviews (conducted in January 2017) with mobile payment ecosystem participants, industry experts, served as the research data, along with literature and publicly available information. The importance of nine success factors (choice of technology, choice of features, size of the ecosystem and openness, security, service pricing, reliable platform provider, guidance, training and support, successful implementation of service changes and sales and marketing of the platform) was evaluated. Because IT governance has been considered successful in the field of IT, two structures, three processes and three relational mechanisms were chosen to be evaluated to see their suitability in a mobile payment ecosystem. To create a better picture of the ecosystem, the perceived roles and responsibilities of the ecosystem participants were examined. All nine success factors were considered greatly significant for the success of a mobile payment platform. The successful implementation of service changes, the choice of technology and marketing of the platform were seen as the most important factors. User support was perceived the least important. Four success factors, user experience, ease of implementation, ability to use in all channels and loose competition and authoritative control, were added by the interviewees. Both cooperation between the ecosystem participants and clearly defined roles and responsibilities were perceived as critical for success. Solutions should also be based on existing standards. Identified contact persons in the participants’ organizations and a defined development plan were considered well-suitable for governing the mobile payment ecosystem.